2019
DOI: 10.1186/s43054-019-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular systolic and diastolic functions in severely malnourished children

Abstract: Background: Malnourished children endure many changes in body composition and lose heart and skeletal muscle mass. Diastolic dysfunction is one of the major causes of heart failure with preserved ejection fraction. Aim: To assess left ventricular systolic and diastolic functions in children with severe acute malnutrition using tissue Doppler imaging technique and to evaluate the effect of nutritional rehabilitation. Patients and Methods: A follow-up case-control study conducted on 60 severely malnourished chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“… 4 In our study we observed that mean (SD) values of EF, fractional shortening (FS) were in normal range, while myocardial performance index (MPI) was abnormal in all children. Similar results were reported by Meena et al, 5 Bebars et al 6 and Akdeniz et al, 7 whereas the median (IQR) values of MPI in normal range, but individual analysis of MPI reveals that 26/88 (29.5%) of children showed abnormal values in a study by Brent et al. 8 This variability in results might be due to difference in severity of phenotypes of SAM and different grade of severity of electrolyte imbalance or trace element deficiency which affect cardiac functions.…”
supporting
confidence: 91%
“… 4 In our study we observed that mean (SD) values of EF, fractional shortening (FS) were in normal range, while myocardial performance index (MPI) was abnormal in all children. Similar results were reported by Meena et al, 5 Bebars et al 6 and Akdeniz et al, 7 whereas the median (IQR) values of MPI in normal range, but individual analysis of MPI reveals that 26/88 (29.5%) of children showed abnormal values in a study by Brent et al. 8 This variability in results might be due to difference in severity of phenotypes of SAM and different grade of severity of electrolyte imbalance or trace element deficiency which affect cardiac functions.…”
supporting
confidence: 91%